Hukum Islam dalam Pergumulan Politik Hukum Nasional Era Reformasi - M. Shohibul Itmam (AL-TAHRIR, 2013)
Abstract: This paper describes the existence of Islamic Law in the plurality of national law amidst the process of the tug of political struggle of national law in reform era. This discussion is focused on the following; first, the struggle of religion, law and politics in Indonesia; second, the development of Indonesian law and politics of law in reform era; third, the opportunities and challenges of Islamic law in the middle of the plurality of national law in reform era. This paper was as a result of library research using legal normative status, historical, and sociological point of view. The result of this study was that the struggle of religion, law and politics in Indonesia was as a process of symbiosis mutualism. Every religion has the same rights in a democratic frame of Pancasila and the 1945 Constitution and the government is as its regulator. The development of law and political law of the reform era indicated that the presence of political sciencetific engineering of Dutch law had resulted in positive law in Indonesia which had not met the legal awareness of the community. In fact, the opportunities and challenges of Islamic law in the middle of the plurality of national law of reform era are formulated in three aspects. Politically, the weak parliamentary support in the National Legislation Program  PROLEGNAS) affects the existence of Islamic law. Philosophically, the internal conflict in the understanding of Islamic law sometimes marginalize Islamic law itself. And sociologically, only few values of Islamic law are absorbed in a national scale.